Synthesis and reactivity of aliphatic sulfur pentafluorides from substituted (pentafluorosulfanyl)benzenes - Vida, Norbert; Václavík, Jiří; Beier, Petr (Beilstein Journal of Organic Chemistry, 2016)
Oxidation of 3- and 4-pentafluorosulfanyl-substituted anisoles and phenols with hydrogen peroxide and sulfuric acid provided a mixture of SF5-substituted muconolactone, maleic, and succinic acids. A plausible mechanism for the formation of the aliphatic SF5 compounds was presented and their chemical reactivity was investigated. SF5-substituted para-benzoquinone was synthesized; its oxidation led to an improved yield of 2-(pentafluorosulfanyl)maleic acid. The reaction of SF5-substituted maleic anhydride and para-benzoquinone with cyclopentadiene afforded the Diels–Alder adducts. Decomposition of 3-(pentafluorosulfanyl)muconolactone in acidic, neutral and basic aqueous media was investigated and the decarboxylation of 2-(pentafluorosulfanyl)maleic acid provided 3-(pentafluorosulfanyl)acrylic acid.
Keywords: dearomatization; decarboxylation; Diels–Alder reaction; oxidation; pentafluorosulfanyl group